Effects of mothers' socio-economic status on the management of febrile conditions in their under five children in a resource limited setting - Ayandiran Olufemi E; Adebayo Abayomi A; Olaogun Adenike AE; Olasode Olayinka A (BMC, 2006)
Abstract Background Public health research is shifting focus to the role of socioeconomic indicators in the promotion of health. As such an understanding of the roles that socio-economic factors play in improving health and health-seeking behaviour is important for public health policy. This is because the share of resources devoted to different policy options should depend on their relative effectiveness. Objective To measure the effect of socio-economic status (age, education, occupation, income, religion and family structure) of mothers on the management of febrile conditions in under-fives children Method Two hundred mothers who brought their febrile under-five children to a health facility were interviewed on the treatment they gave to their children before reporting at health facility. Data collected were entered and analyzed using the SPSS software. Binary logistic regression was adopted for the quantitative analysis of the effect of socio-economic variables on the mothers' actions prior to utilizing the health facility. Results Results showed that while mothers' age was negatively correlated (-0.13), occupation was positively correlated (0.17) with under-fives mothers' action. Education, religion, income and family structure were however insignificant at 5% level Conclusion This poses a lot of challenges to policy makers in the developing nations where women's education and earning capacity is low. There is therefore a need to increase the number of women benefiting from micro credit. This will ensure that more women are engaged in a form of occupation that is profitable and can sustain the economic and health needs of the family.